Laporan Kasus: Retardasi Mental Berat Pada Remaja Usia 16 Tahun dengan Riwayat Epilepsi Tidak Terkontrol - Aziz, Rachman; Jiofansyah, Jiofansyah; Septa, Tendry (CV. Jasa Sukses Abadi, 2024)
Mental retardation (MR), also known as Intellectual Disability (ID), is a lifelong mental disorder characterized by significant cognitive and adaptive impairments, often associated with structural or functional brain anomalies and diverse etiologies that frequently co-occur with conditions such as epilepsy. In Indonesia, a survey conducted in 2012 revealed that 2.45% of the population had disabilities, including individuals with mental retardation. The World Health Organization (WHO) estimates the prevalence of mental retardation in Indonesia to be around 1-3% of the population, with one-quarter of cases classified as moderate to severe mental retardation. The occurrence of mental retardation is closely linked to a child's developmental trajectory, influenced by genetic and environmental factors. In terms of pathogenesis, the onset can originate from prenatal, perinatal, or postnatal factors, with various contributing elements, including a history of seizures. The severity levels are classified as mild, moderate, severe, or profound mental retardation. Epilepsy is a common neurological disorder in children, often co-occurring with mental retardation, found in 25% of cases. The occurrence of epilepsy can either accompany or be the cause of mental retardation, leading to a classification known as Developmental and Epileptic Encephalopathy (DEE). This case report will present the case of a teenager with mental retardation who has a history of recurrent seizures, illustrating the complex relationship between these two conditions. Hence, there is a need for a comprehensive approach and increased awareness in diagnosing and managing children with concurrent mental retardation and epilepsy with the goal of providing optimal care.